Islamic Boarding School Based on Women’s Empowerment and Equality - Elly Malihah; S Nurbayani; Puspita Wulandari; Wilodati Wilodati; M.F. Husaeni; R Hartono; S.B. Agista; S.A. Rahmah; Y.A. Kesumah (Komunitas, 2023)
Islamic boarding schools in Indonesia are often considered an important aspect of religious education. One aspect of the discussion that is rarely discussed in Islamic boarding schools is women's empowerment and gender equality because this is often considered an idea derived from western ideology and education. However, to solve the country's economic and development problems, ideas and discussions around gender equality and women's empowerment are now increasingly coming to the fore and becoming a public concern. One of the institutions that became the focus of this research was the involvement of Islamic boarding schools in teaching these ideas to their students. Thus, the main question in this study is how gender and women's empowerment are implemented in Islamic boarding schools. This study uses a qualitative approach with phenomenological studies to explore and identify existing field results by carrying out field observations and interviews with various speakers including educators and students as the primary method of data collection. Observations and interview questions are based on research formulations that focus on the practice and involvement of institutions and each Islamic boarding school actor in gender equality and women's empowerment. The results illustrate the role of an educational institution that optimizes education based on gender equality and women's empowerment in its curriculum. In addition, each individual also has an active role in efforts to empower women to change the negative stigma brought by conservative Islamic understanding of women. Education in Islamic boarding schools also actively tackles radicalism among its students. This study discusses how Islamic boarding schools in Tasikmalaya are reforming their curriculum and environment to assimilate with gender education and women's empowerment.